A Study on Distribution Strategies of Steel Manufacturers in India - Dasari, Shailendra (Indian Journal of Marketing, 2012)
Steel industry in India is poised for a big growth. Post 1990, thanks to the liberalization of the Indian economy, steel manufacturers have been focusing upon becoming customer-centric, as opposed to the selling approach that had prevailed for more than four decades, to match up to the competition from local and global players. Distribution of steel in this context assumes a lot of importance looking at the bulky nature of the product and changing needs and expectations of customers. This paper attempts to trace the evolution of distribution systems adopted by steel producers, current strategies and future trends in the form of case studies of all the major steel manufacturers and service centers throughout the country.